From Roller Coasters to Rocket Ships: Lessons from Past Successes in African Agriculture - Haggblade, Steve; Ehui, Simeon K. (2010)
IFPRI Policy Seminar "Successes in African Agriculture" by Peter Hazell, Steve Haggblade and Simeon Ehui on 24th June, 2010.